2003
DOI: 10.4049/jimmunol.171.7.3467
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor-Derived Heat Shock Protein 96 Mediates In Vitro Activation and In Vivo Expansion of Melanoma- and Colon Carcinoma-Specific T Cells

Abstract: Heat shock proteins (hsp) 96 play an essential role in protein metabolism and exert stimulatory activities on innate and adaptive immunity. Vaccination with tumor-derived hsp96 induces CD8+ T cell-mediated tumor regressions in different animal models. In this study, we show that hsp96 purified from human melanoma or colon carcinoma activate tumor- and Ag-specific T cells in vitro and expand them in vivo. HLA-A*0201-restricted CD8+ T cells recognizing Ags expressed in human melanoma (melanoma Ag recognized by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 25 publications
2
63
1
2
Order By: Relevance
“…As for the human system, HSPs purified from human tumors or virus-infected cells have been shown to induce a CTL response in vivo and in vitro against a variety of Ags expressed by the cells from which these immunogenic proteins were purified, confirming that the HSP immunological properties are fully maintained in the human setting (54,55). In fact, using an autologous system, we and others (54 -56) were able to show that in vitro stimulation of patients' PBMCs with melanoma-derived Hsp70 and Gp96 elicited tumor-specific T cells and that these T cells included effectors directed not only against melanoma-shared Ags but also against an individual Ag generated by a mutation occurring in the a tyrosine phosphatase receptor protein (receptor-type protein-tyrosine phosphatase K) (Ref.…”
Section: Implications For Immunotherapymentioning
confidence: 97%
“…As for the human system, HSPs purified from human tumors or virus-infected cells have been shown to induce a CTL response in vivo and in vitro against a variety of Ags expressed by the cells from which these immunogenic proteins were purified, confirming that the HSP immunological properties are fully maintained in the human setting (54,55). In fact, using an autologous system, we and others (54 -56) were able to show that in vitro stimulation of patients' PBMCs with melanoma-derived Hsp70 and Gp96 elicited tumor-specific T cells and that these T cells included effectors directed not only against melanoma-shared Ags but also against an individual Ag generated by a mutation occurring in the a tyrosine phosphatase receptor protein (receptor-type protein-tyrosine phosphatase K) (Ref.…”
Section: Implications For Immunotherapymentioning
confidence: 97%
“…A phase III clinical trial using heat shock proteins (HSP) extracted from autologous tumour (Oncophage, Antigenics, New York, NY) was developed. In the cell, these proteins act as ''chaperones'' for peptide antigens and have the potential to present tumour antigens to the immune system (Rivoltini et al, 2003;Lewis, 2004). Even though the preliminary results indicated no statistically significant effect for the heat shock vaccine compared with the physician's choice of therapy, an intriguing observation of this trial is that the group of patients with M1 stage of disease treated with the vaccine, lived longer than those receiving other therapy, although not significant (Antigenics press release, 2005).…”
Section: Autologous Tumour Vaccinesmentioning
confidence: 99%
“…142,143 Eventually, Hsc70/Hsp70 and Gp96 even made their way from bench to bedside (Tables 1 and 2; http://www.clinicaltrials.gov). [144][145][146][147][148][149][150][151][152][153][154][155][156] 1 The most commonly used designations for the HSP families and the individual HSPs are used. The recently proposed new nomenclature is provided in brackets for the respective human HSPs.…”
Section: Discovery Of Hsps Gp96 and Their Immunological Propertiesmentioning
confidence: 99%
“…Furthermore, vaccination with autologous tumor-derived Gp96 even led to an expansion of specific T cells in vivo. 147 Unfortunately, no clinical benefit could be observed. Concerning the contrast between induction of a tumor-specific immune reaction on the one hand and lack of a positive clinical response on the other hand, it should be mentioned that Rosenberg et al 170 reported similar observations in melanoma patients, showing tumor progression despite detection of large numbers of melanoma-specific 176 Clinical use of corresponding tools is under way, for example, applying the anti-CD25 Ab daclizumab to target regulatory T lymphocytes or the anti-CTLA-4-antibody Ipilimumab.…”
mentioning
confidence: 99%